Beyond the European Semester: The supranational evaluation cycle for pensions. (December 2022) - Guardiancich, Igor; Guidi, Mattia; Terlizzi, Andrea
Pensions at the European level have been, since the sovereign debt crisis, affected by several decision-making innovations. Retirement policy has been embedded in the European Semester, which strengthened the hitherto inadequate European socioeconomic policy coordination mechanisms. Given that the additional powers bestowed upon the Commission were qualified, a supranational response followed. With the effect of strengthening its rational-legal authority, in line with neo-functionalist spillover assumptions, evidence-based standards have been progressively applied to EU retirement policy formation. This innovative turn warrants the employment of a policy analysis theoretical framework. In particular, the article applies the concepts underpinning policy evaluation to the study of pensions within the Semester. Using a mixed-methods approach, which combines case study with statistical analysis, and following a novel in-depth coding of country-specific recommendations and Country Reports, this article argues that member states' pensions are now assessed within a structured, formal and polycentric evaluation cycle. This has been gradually constructed by increasing the coherence between the yearly interim ex post evaluations of pension policy output (the Country Reports) and the final ex post evaluations of pension policy outcomes (the Ageing and Pension Adequacy Reports) that are published every 3 years. The result is a streamlined, technocratic, knowledge-based approach to retirement policy at the supranational level. Even though the generation of technical knowledge is no substitute for toothless conditionality, greater reliance on evidence is aimed at socializing national decision-makers and may eventually influence their policy choices. The unconventional pension evaluation cycle that sprung up around the Semester may, hence, serve as a model applicable to other socioeconomic policy domains.